Sports despite masks: no negative effects of FFP2 face masks on cardiopulmonary exercise capacity in children - Weigelt, Annika; Schöffl, Isabelle; Rottermann, Kathrin; Wällisch, Wolfgang; Müller, Susanna; Dittrich, Sven; Hübner, Matthias (European Journal of Pediatrics, 2023)
Face masks were recognized as one of the most effective ways to prevent the spread of the COVID-19 virus in adults. These benefits were extended to children and adolescents. However, the fear of negative consequences from wearing a face mask during physical exercise led to cancellations of physical education lessons. This further decreased the amount of physical activity available to children and adolescents during the pandemic. However, there is little published data on the potential adverse effects of wearing the most effective and partially mandatory FFP2/N95 face masks during PE or physical activity (PA) in this age. Even though the pandemic has been declared as passed by the WHO, the rise of a new pandemic and thus the use of face masks for limiting its spread is inevitable, so we need to be better prepared for alternative options to lockdown and limitation of PA in such a scenario. Twenty healthy children aged 8–10 years performed two identical cardiopulmonary exercise tests as an incremental step test on a treadmill within an interval of 2 weeks, one time without wearing a protective mask and one time wearing an FFP2 mask. The cardiopulmonary exercise parameter and especially the end-expiratory gas exchange for oxygen and carbon dioxide (petO2 and petCO2) were documented for each step, at rest and 1 min after reaching physical exhaustion. Twelve boys (mean age 8.5 ± 1.4 years) and 8 girls (mean age 8.8 ± 1.4 years) showed no adverse events until maximal exertion. The mean parameters measured at peak exercise did not differ significantly between both examinations (mean peak VO2 = 42.7 ± 9.5 vs 47.8 ± 12.9 ml/min/kg, p = 0.097, mean O2pulse 7.84 ± 1.9 ml/min vs. 6.89 ± 1.8, p = 0.064, mean VE/VCO2slope 33.4 ± 5.9 vs. 34.0 ± 5.3, p = 0.689). The only significant difference was the respiratory exchange rate (RER, 1.01 ± 0.08 vs 0.95 ± 0.08, p = 0.004). The measured respiratory gases (end-tidal O2 and CO2) decreased and respectively increased significantly in almost every step when wearing an FFP2 mask. However, these levels were well below hypercapnia and above hypoxia. Conclusion: In this study, no significant differences in the cardiorespiratory function at peak exercise could be discerned when wearing an FFP2/N95 face mask. While the end-tidal values for CO2 increased significantly and the end-tidal values for O2 decreased significantly, these values did never reach levels of hypercapnia or hypoxia. Furthermore, the children terminated the exercise at a lower RER and heart rate (HR) suggesting a subconscious awareness of the higher strain. Since the detrimental effects of limiting sports during the pandemic are well documented, stopping PE lessons altogether because of the minor physiological effects of wearing these masks instead of simply stopping pushing children to perform at their best seems premature and should be reconsidered in the future. What is Known: • Wearing a face mask has an influence on psychological, social, and physiological functions in adults. • Because of the observed effects of wearing face masks in adults, physical activity in children was limited during the pandemic. What is New: • Wearing an FFP2/N95 mask during physical activity did not lead to hypercapnia or hypoxia in children in this study. • Even though end-tidal CO2 values were significantly higher and end-tidal O2 values significantly lower when wearing an FFP2/N95 face mask, no pathological values were reached.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Coronavirus; COVID-19; End-tidal CO; End-tidal O; Oxygen saturation; Treadmill testing; VO